Juridical Analysis of the Responsibility of Social Media Platforms for Cyber Threats Against Digital Activists in Indonesia - Siti Hapsah Fahira; Daimah Daimah; Irkham Mu'amar Mu'amar; Akpoghome Theresa (Indonesian Cyber Law Review, 2025)
The increasing intensity of cyberattacks against digital activists in Indonesia highlights the urgency of re-reading the responsibilities of social media platforms as providers of digital space. Attacks in the form of doxing, hacking, and intimidation not only threaten freedom of expression, but also create inequality in legal protection for vulnerable groups. This research aims to juridically analyze the legal responsibility of digital platforms for cyber threats experienced by activists in Indonesia, and formulate a more adaptive and human rights-based regulatory framework. The method used is a normative-empirical approach, with data collection techniques through documentation studies, in-depth interviews with activists and legal experts, as well as analysis of laws and regulations and internal platform policies. The results showed that the majority of platforms failed to carry out the principle of due diligence and only followed up on a small portion of the reports submitted. On the other hand, the absence of national legal norms that explicitly regulate the responsibility of platforms also weakens legal protection for victims. This research recommends the establishment of new norms based on shared responsibility and the integration of digital human rights principles in national laws and regulations. The findings emphasize the importance of a regulatory approach that is not only reactive, but also preventive and accountable in dealing with threats to civil liberties in the digital space.